The impact of crime on foreign direct investment - Muhammad Mukhlis Afriyanto (Economic Journal of Emerging Markets, 2017)
This study examines the impact of crime incidence on Foreign Direct Investment (FDI) in Indonesian provinces. This study uses panel data covering 31 provinces for the period 2005 to 2015. We involve Total Crime, Property Crime, Violence, Vandalism, Arson, Fraud, Homicides and Kidnapping as variable of crime. The results show that crime variables have significant impact on FDI. We find that for every increase in total crime incidence per 100,000 people by ten percent, FDI is expected to decrease by approximately 0.95 percent. The results of this study suggest that besides boosting economic growth, stimulating infrastructure development, and lowering the provincial minimum wages, government needs to pay attention to crime incidence in each province. Government should allocate adequate resources to minimize the crime rate.